COMPARİSON OF STATE ANXİETY LEVEL OF SPORTSMEN BEFORE AND AFTER COMPETİTİON İN TURKEY ELDERS WRESTLİNG NATİONAL TEAM - Serhat Ozbay; Yildiz Mustafa (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The aim of this research is to compare the state anxiety level of sportsmen who will take part in World Championship Competition.7 greco-roman aged between 17 and 34 who took part in World Championship in a National Wrestling Team, and 7 freestyle totally 14 men and 7 women joined the research. State Trait Anxiety Iventory (STAI) was used in the survey. In its solution and comment, Paried Samples t tests were used in State Anxiety level of sportsmen before and after competition and One Way Anova test were used sportsmen's state anxiety levels before and after competion in Wrestling National Team according to weight variant. In evoloting datum and finding the calculated volve SPSS (Statistical package for social sciences) was used. Difference of State Anxiety level of sportsman before and after competition in Wrestling National Team was determined meaningful [p<0.05]. The difference of state anxiety level of woman player before and after competition was determined meaningful [p<0.05]. The difference of state anxiety level of woman player before and after competition was determined meaningless [ p>0.05]. According to weight variant the difference of state anxiety level of sportsmen before and after competition in Wrestling National Team was determined meaningless [ p>0.05]. To sum up whatever sex,weight of sportsmen are, they need certain anxiety level for performance and concentration. The experience and personal charecteristics of sportsmen is important in low or high level of this type of axiety. In addition to tactic exercise in trainer exercise, they should put emphasis on paining skills and improving skills.